Islamic Self‑Respect as a Coping Strategy for Victims of Sexual Harassment - Nur Afiah; Rezki Perdani Sawai; Ros Aiza Binti Mohd Mohktar (LPPM IAIN Parepare, 2025)
Victims of sexual abuse in Muslim communities often face limited access to psychosocial support due to stigma, shame, and the lack of culturally and religiously relevant interventions. This study addresses these challenges by examining how Islamic values, izzah (dignity), sabr (patience), and tawakkul (trust in God) can support the development of self-esteem as a coping strategy for victims. Using a Systematic Literature Review (SLR) combined with bibliometric analysis through VOSviewer software, this study explores how these core Islamic concepts contribute to psychological resilience. The findings reveal that self-esteem rooted in Islamic spirituality plays a critical role in helping victims cope with trauma and rebuild their psychological well-being. Islamic values offer not only personal spiritual strength but also a culturally appropriate framework for recovery, especially in communities where modern mental health services are underutilized. An approach based on sabr, tawakkul, and izzah can strengthen resilience and restore self-worth affected by abuse. This study provides valuable insights for scholars, mental health practitioners, and policymakers, emphasizing the need for interventions and policies grounded in Islamic teachings to support survivors in Muslim communities.